2012
DOI: 10.1007/s11627-012-9439-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of purple pitahaya (Hylocereus costaricensis [F.A.C. Weber] Britton & Rose) cv. Cebra

Abstract: Limitations to large-scale propagation of purple pitahaya (Hylocereus costaricensis [F.A.C. Weber] Britton & Rose), a potential source of betalains for the food industry, can be overcome through utilization of in vitro culture technologies. In this work, successful in vitro propagation from areoles of adult purple pitahaya plants is reported. Factors affecting culture initiation, bud sprouting and growth, shoot multiplication, rooting, and acclimatization were studied. Best results for culture initiation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 30 publications
(49 reference statements)
1
14
0
12
Order By: Relevance
“…very few starting materials. Currently, several researchers have established protocols for propagation of pitaya (Infante 1992;Drew and Azimi 2002;Mohamed-Yasseen 2002;Pelah et al 2002;Viñas et al 2012;Fan et al 2013). However, pitaya with diverse genetic backgrounds respond differently to the same culture medium, probably due to genetic conditioning (Drew and Azimi 2002;MohamedYasseen 2002;Fan et al 2013).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…very few starting materials. Currently, several researchers have established protocols for propagation of pitaya (Infante 1992;Drew and Azimi 2002;Mohamed-Yasseen 2002;Pelah et al 2002;Viñas et al 2012;Fan et al 2013). However, pitaya with diverse genetic backgrounds respond differently to the same culture medium, probably due to genetic conditioning (Drew and Azimi 2002;MohamedYasseen 2002;Fan et al 2013).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…TDZ, ZT, 6-BA and 2, 4-D are commonly used for shoot regeneration in many plant species (Ellis et al 1991;Huetteman and Preece 1993). Micropropagation of pitaya has been achieved using TDZ or 6-BA alone (Mohamed-Yasseen 2002; Viñas et al 2012;Fan et al 2013), however, the role of ZT and 2, 4-D in pitaya propagation is not reported yet. In this study, we found that pitaya explants were more sensitive to TDZ than ZT, 6-BA and 2, 4-D (Supplementary Tables 1-4 and Supplementary Fig.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…On the other hand, there are some reports of success of micropropagation in dragon fruit. According to Vinas et al 2012, central region of new joint as explant showed about 100 percent survival rates and the growth was higher compare to basal and distal joints.…”
Section: Introductionmentioning
confidence: 99%
“…In culture initiation and axillary bud growth of purple pitahaya (Hylocereus costaricensis) larger explants (5 to 7 cm length) was sterilized with alkaline detergent for 10 min, followed by immersion in 70% (v/v) ethanol for 15 to 30 s, a mixture of fungicide and bactericide for 30 min, In vitro micrografting of lucumo and disinfection in sodium hypochlorite (1.0% v/v) for 15 min, which resulted in a significant reduction of the level of damage to only 16% of the explants, and the abscence of contamination (Viñas et al 2012). These results were very similar to the ones observed in our study, where the disinfection method we used produced contamination rates comparable with the best results published for in vitro trees species using field explants (Işıkalan et al 2011;Cortizo et al 2004).…”
Section: Culture Initiationmentioning
confidence: 99%